Continuous Long-Term Physical Activity Monitoring in Hemodialysis Patients. Issue 9 (29th September 2022) - Cohen, Brandon; Munugoti, Samhitha; Kotwani, Sonia; Randhawa, Lovepreet S.; Dalezman, Solomon; Elters, Antonio C.; Nam, Kate; Ibarra, Jose S.; Venkataraman, Sandheep; Paredes, William; Ohri, Nitin; Abramowitz, Matthew K.
Visual Abstract: Abstract : Key Points: Long-term continuous use of wrist-worn accelerometers is acceptable to patients receiving hemodialysis and is well tolerated. In patients with substantial comorbidity, the highest intensity of physical activity occurred in the hour immediately after hemodialysis. Recognition of increased activity after dialysis may create an opportunity for clinicians and dialysis staff to promote physical activity. Background: Physical inactivity is common in patients receiving hemodialysis, but activity patterns throughout the day and in relation to dialysis are largely unknown. This knowledge gap can be addressed by long-term continuous activity monitoring, but this has not been attempted and may not be acceptable to patients receiving dialysis. Methods: Ambulatory patients with end-stage kidney disease receiving thrice-weekly hemodialysis wore commercially available wrist-worn activity monitors for 6 months. Step counts were collected every 15 minutes and were linked to dialysis treatments. Physical function was assessed using the Short Physical Performance Battery (SPPB). Fast time to recovery from dialysis was defined as ≤2 hours. Mixed effects models were created to estimate step counts over time. Results: Of 52 patients enrolled, 48 were included in the final cohort. The mean age was 60 years, and 75% were Black or Hispanic. Comorbidity burden was high, 38% were transported to and from dialysis by paratransit, and 79% had SPPB <10. Median accelerometer use (199 days) and adherence (95%) were high. Forty-two patients (of 43 responders) reported wearing the accelerometer every day, and few barriers to adherence were noted. Step counts were lower on dialysis days (3991 [95% CI, 3187 to 4796] versus 4561 [95% CI, 3757 to 5365]), but step-count intensity was significantly higher during the hour immediately after dialysis than during the corresponding time on nondialysis days (188 steps per hour increase [95% CI, 171 to 205]); these levels were the highest noted at any time. Postdialysis increases were more pronounced among patients with fast recovery time (225 [95% CI, 203 to 248] versus 134 [95% CI, 107 to 161] steps per hour) or those with SPPB ≥7. Estimates were unchanged after adjustment for demographics, diabetes status, and ultrafiltration rate. Conclusions: Long-term continuous monitoring of physical activity is feasible in patients receiving hemodialysis. Highly granular data collection and analysis yielded new insights into patterns of activity after dialysis treatments.